Immunohistochemical Assessment of Mast Cells and Small Blood Vessels in Dentigerous Cyst, Odontogenic Keratocyst, and Periapical Cyst - Maryam Kouhsoltani; Monir Moradzadeh Khiavi; Golshan Jamali; Samira Farnia (Tabriz University of Medical Sciences, 2015)
Purpose: The aim of this study was to verify the density of mast cells (MCs) and microvessels in odontogenic cysts. Furthermore, the correlation between MCs and microvessels was evaluated to assess the contribution of MCs to angiogenesis and growth of odontogenic cysts. This approach may be a basis for the development of future pharmaceuticals addressed to MCs performance to manage odontogenic cysts. To our knowledge, no study investigating the correlation between MCs and microvessels has been performed to date. Methods: 60 cases of odontogenic cysts consisting of 20 radicular cysts (RCs), 20 odontogenic keratocysts (OKCs) and 20 dentigerous cysts (DCs) were included in this study. Five high power fields in superficial connective tissue and five high power fields in deep connective tissue were counted for each sample. Moreover, a total mean of ten fields was calculated. Results: RC showed the highest mean numbers of MCs and microvessels (p<0.05). The subepithelial zones of all cysts contained more MCs and microvessels compared to the deeper zones. A statistically significant correlation between the numbers of MCs and microvessels was not observed (r=0.00, p=0.49). Conclusion: Although the number of MCs was not significantly associated with microvessels, these cells may be related to the growth of odontogenic lesions, particularly RCs. Further studies on the in vivo functions of MCs will make the concept more clear.